Post-colonialism and Political Satire in South Africa - Enas Abdallah Abdelwahab Abdelkader (Maǧallaẗ Kulliyyaẗ Al-ādāb Ǧāmiʿaẗ Būrsaʿīd, 2020)
South Africa suffered from the British colonial rule after which the Dutch settlers took over the country and exercised an excessive discriminatory regime. This research explores the ways through which political satire was able to reflect the post-colonial situation in Peter Horn's poems and his use of such technique to revive the spirit of liberty in the South Africans and to highlight the fact that the colonial regime led to the deterioration of many moral and religious values.